SEQEL: a tool for biological sequence manipulation in Emacs - Xu, Zhenjiang Zech; Lu, Hui (Bioinformatics Advances, 2021)
Summary Sequences are arguably the most common biological data. An easy-to-use tool can greatly facilitate daily manipulation and analysis of biological sequences. Here, we present SEQEL, a tool providing a convenient environment for editing, formatting and rendering of DNA, RNA and protein sequences. This is accomplished by extending the commonly used text editor, Emacs, which is available for Windows, Linux and Mac OS. Availability and Implementation The unit tested ELISP source code for seqel is freely available from https://github.com/rnaer/seqel along with documentation. Contact zhenjiang.xu@gmail.com